(untitled) (Journal of Medicine, 2019)
Background: Attempted suicide or deliberate self-harm by self-poisoning among adult males and females are a major public health problem to be addressed like any other medical condition. In recent years, patterns of self-poisoning are changing. So it is important to know about the substances used in self poisoning and its outcome. Materials and Methods: It was a descriptive type of cross sectional study done in Department of Medicine, Dhaka medical college hospital, Dhaka on100 patients with a history of self-poisoning. Study period was six months. A semi structured questionnaire was used for collection of data. Results: In our study self-poisoning was more prevalent among young age group with female preponderance. Family disharmony (45%) was the commonest cause of self poisoning and most commonly used substance was pharmaceutical drugs. Anxiolytics were the commonest (42 %), organo phosphorus compound (OPC) 20%, mixed drugs 12%, harpic 11%, rat killer 8%, NSAIDs 3%, Dettol 3% and Wheel powder 1%. Out of 90 patients 91.11% patients recovered completely. Death was observed from OPC poisoning. Conclusion: Knowing the pattern and outcome of self poisoning may improve the community based support system through which we can combat against self- poisoning. J MEDICINE JAN 2020; 21 (1) : 20-25